Structural evolution with martensite formation in copper based shape memory alloys - Adigüzel, Osman (My University, 2007)
A series of alloy systems, in particular copper-based ?-phase alloys and NiTi alloys exhibit a peculiar property called shape memory effect. Metastable ?-phases of noble metal copper based ternary alloys have commonly bcc structure and homogenise as B2(CsCl) or DO3 (Fe 3Al) type ordered structures at high temperatures. In some cases, L21 (Cu2AlMn)-type ordered structures occur instead of DO3 (Fe,3Al)-type structures. - These ordered structures martensitically undergo to the layered structures on cooling from high temperatures. Martensitic transformations occur by two or more lattice invariant shears on a (110}-type plane of austenite matrix which is basal plane or stacking plane for martensite. The order of martensite structure is closely related to the order of parent austenite due to the displacive character of the transformation, and the martensite inherits the order of parent existing prior to the transformation. The product martensites have the unusual complex structures called long period layered structures such as 2H, 3R, 9R or 18R depending on the stacking sequences on the close-packed planes of the ordered lattice. - The layered structures of ?-type martensites are characterized by the stacking sequences depending on the order in parent ?-phase condition due to the diffusionless character of the transition. In case the parent phase has a B2-superlattice, the stacking sequence is ABCBCACAB(9R). If the parent phase has a DO3-type superlattice, the stacking sequence becomes ABCBCACABABCBCACAB(18R) in martensitic case. On the other hand, monoclinic distortion takes place in some cases and 18R structure is modified as M18R. This sequence is more complex in L21 (Cu2AlMn) case of parent phase. - The fundamental structures of the ?-type martensites are orthorhombic closepacked structures, which consist of an array of close-packed planes. The {110}-type plane of matrix which is the basal plane for martensite is subjected to the hexagonal distortion with martensite formation, and atom sizes have important effect on the hexagonal distortion. These properties have been investigated on shape memory CuZnAl and CuAIMn alloys.
Keywords: Copper based alloys; Hexagonal distortion; Layered structures; Martensite Formation; Shape memory alloy